Effect of astigmatism on visual outcomes after multifocal intraocular lens implantation: a systematic review and meta-analysis - Shen, Wenqian; Zhuo, Baoxian; Zhang, Limei; Shen, Jiying; Ma, Dongmei; Yang, Jin (Frontiers in Medicine, 2023)
Purpose: To investigate the effects of postoperative astigmatism on the visual outcomes following presbyopia-correcting surgery with multifocal intraocular lens implantation.A comprehensive literature search was conducted using PubMed, Embase, and Web of Science for articles published until January 2023. Additionally, we included retrospective case series and prospective comparative studies. The combined mean difference (MD) with 95% confidence intervals (CI) and odds ratio (OR) with 95% CI were used to express continuous and categorical outcomes, respectively. All statistical analyses were performed using Review Manager (version 5.4.1).We included nine eligible studies that analyzed 3088 eyes. The proportion of eyes with useful postoperative visual acuity (logMAR ≤ 0.20) and residual astigmatism significantly differed with respect to the magnitude of astigmatism and presence/absence of blurred vision (P < 0.001 for both). Additionally, the mean uncorrected distance visual acuity (MD, 0.14; 95% CI, 0.06 to 0.21; P = 0.0003) and uncorrected intermediate visual acuity (MD, 0.07; 95% CI, 0.00 to 0.13; P = 0.04), but not the uncorrected near visual acuity (MD, 0.02; 95%CI -0.01 to 0.05; P=0.17), significantly differed according to the magnitude of astigmatism.Astigmatism, even at low levels (≥ 0.5D), has a significant effect on visual outcomes, especially on UDVA and UIVA, following multifocal intraocular lens implantation. Accurate preoperative and postoperative evaluation of astigmatism is important.